Antibody-Mediated Virus Neutralization Is Not a Universal Mechanism of Marburg, Ebola, or Sosuga Virus Clearance in Egyptian Rousette Bats. (24th December 2018) - Schuh, Amy J; Amman, Brian R; Sealy, Tara K; Kainulainen, Markus H; Chakrabarti, Ayan K; Guerrero, Lisa W; Nichol, Stuart T; Albarino, Cesar G; Towner, Jonathan S
Abstract: Although bats are increasingly being recognized as natural reservoir hosts of emerging zoonotic viruses, little is known about how they control and clear virus infection in the absence of clinical disease. Here, we test >50 convalescent sera from Egyptian rousette bats (ERBs) experimentally primed or prime-boosted with Marburg virus, Ebola virus, or Sosuga virus for the presence of virus-specific neutralizing antibodies, using infectious reporter viruses. After serum neutralization testing, we conclude that antibody-mediated virus neutralization does not contribute significantly to the control and clearance of Marburg virus, Ebola virus, or Sosuga virus infection in ERBs. Abstract : Testing of >50 convalescent sera from bats experimentally infected with Marburg, Ebola, or Sosuga virus revealed the absence of virus-specific neutralizing antibodies. We conclude that antibody-mediated virus neutralization is not a universal mechanism by which bats control infection with these viruses.